Classroom interaction - Malamah-Thomas, Ann (Oxford University Press, 1999)
This book, in common with others in the scheme, consists of three sections. The first leads the reader into diiferent ways of defining the classroom encounter conceptually in terms of its interactive and communicative features; and operationally in relation to the analysis of different aspects of learner and teacher activity. Section two provides the opportunity for readers to subject to critical scrutiny, informed by their own teaching experience, the schemes that have been devised for the systematic description of classroom behaviour, and various recent approaches to pedagogy which have particular implications for the learner's participation in classroom interaction. In section three, the reader is then provided with the means for exploring by direct application the ideas and practices considered in the previous sections, so that the extent of their relevance and feasibility can be evaluated in the actual process of teaching.